Radiological Evaluation of Uncinate Process Variations using Multidetector Computed Tomography - Khadka, Roshana; Pathak, Manish Raj; Khanal, Bipin; Shah, Rajeev Kumar (Nepal Journal of Medical Sciences, 2023)
Introduction: Functional endoscopic sinus surgery has emerged as a superior technique in sinus surgery with a lower incidence of associated complications as compared to traditional surgeries; however, it still carries risks of possible complications, some of which could be attributable to the variations that exist in the nose and paranasal sinus anatomy. Variations in the uncinate process, one of the important structural landmarks in functional endoscopic sinus surgery can have implications during sinus surgery. Therefore, identifying the variations in the uncinate process becomes a very important consideration. The objective of this study was to identify the variations of the uncinate process on Multidetector Computed Tomography of paranasal sinuses Methods: This cross-sectional study was conducted in the Department of Radiodiagnosis, Birat Medical College and Teaching from December 2021 to June 2022 after obtaining ethical clearance from IRC. A total of 240 participants referred to the Department of Radiodiagnosis for CT of paranasal sinuses were included in the study. Results: The most frequent superior attachment of uncinate was found to be Type I and the least common was Type IV. The least frequent variation was UP pneumatisation. Most of the cases showed typical angulation followed by medial orientation and lateral orientation. Conclusion: Variations in the uncinate process exist and Multidetector CT is a commendable tool for identifying these variations.